Mortar mixing using treated wastewater feasibility. (17th October 2022) - Zahra Bouaich, Fatima; Maherzi, Walid; Benzerzour, Mahfoud; Taleb, Mustapha; Abriak, Nor-Edine; Rais, Zakia; Senouci, Ahmed
Highlights: The mortars based on CEMI and CEM II and treated wastewater had a slight increase in setting times. Treated wastewaters had a slight impact on fresh mortar density for various cement types. Mortars based on CEM III cement and treated wastewater have better mechanical performance. The pouzzolanic reactions for mortar made with CEMIII cement and wastewater that produce a supplementary CSH and ettringite in long term. Abstract: Water scarcity is considered to be one of the most important problems faced by the world today. To alleviate this problem, it is important to study the feasibility of replacing partially or completely potable water for concrete production by treated wastewater. This paper studies the feasibility of using treated wastewater (TWW) from the Artois-Picardy Water Agency in Douai (Hauts de France-France region) for mortar mixing. The aims of this study is to limit watercourse discharges, reduce groundwater over-exploitation, and minimize natural resource pollution. To do this, three series of mortar mixtures have been formulated according to the NF EN 196 standard, varying the type of cement (CEMI CEMII and CEMIII) and mixed with treated wastewaters with a 0.5 water to cement (W / C) ratio. The performance of these mortar mixes were compared to the control ones (mixed with "drinking water" (DW)). The Experimental work included the workability, setting time, and density of different mortar mix designs using treated wastewater. In addition, the dynamic modulus of the mortar (Edyn) was determined, as well as the mechanical properties (compressive and flexural strength) at 7, 28, 60, 90, and 360 days after the mortar samples were made. Furthermore, the environmental assessment of the hardened mortars was evaluated by leaching tests according to the EN 1245–74 standard. The results obtained shown that TWWs had no adverse effect on physical properties (curing time, slump, porosity distribution, and density) of these mortars. On the other hand, the mortar mechanical properties were slightly lower than those of the control for samples made with cement CEM I and CEM II. However, a significant compressive strength increase was recorded for mortars made with CEM III cement. The mortar curing time, slump, and density made with TWW were closer to those of the control.. The hardened mortars were then analyzed by scanning electron microscopy (SEM), and by Thermogravimetric Analysis (TGA) and differential Thermogravimetric Analysis (DTA). According to the obtained findings, the TWW of the city of Douai France could be used for the manufacture of mortar and concrete.